2015
DOI: 10.1111/gcb.12850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity is related to climatic variation and vulnerability in threatened bull trout

Abstract: Understanding how climatic variation influences ecological and evolutionary processes is crucial for informed conservation decision-making. Nevertheless, few studies have measured how climatic variation influences genetic diversity within populations or how genetic diversity is distributed across space relative to future climatic stress. Here, we tested whether patterns of genetic diversity (allelic richness) were related to climatic variation and habitat features in 130 bull trout (Salvelinus confluentus) pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 106 publications
3
53
2
1
Order By: Relevance
“…For a standard panel of 10-15 loci, in open populations (for example, populations with migration and/or admixture, as for Murray cod), HL should also be more correlated with genome-wide homozygosity and inbreeding coefficients than are other common individual-based measures: internal relatedness and the uncorrected proportion of homozygous loci (Aparicio et al, 2006). Our panel of loci is comparable to other studies that have found associations between intraspecific genetic variation and environment (for example, Faulks et al, 2011;Kovach et al, 2015).…”
Section: Individual-based Measure Of Genetic Variationsupporting
confidence: 68%
See 2 more Smart Citations
“…For a standard panel of 10-15 loci, in open populations (for example, populations with migration and/or admixture, as for Murray cod), HL should also be more correlated with genome-wide homozygosity and inbreeding coefficients than are other common individual-based measures: internal relatedness and the uncorrected proportion of homozygous loci (Aparicio et al, 2006). Our panel of loci is comparable to other studies that have found associations between intraspecific genetic variation and environment (for example, Faulks et al, 2011;Kovach et al, 2015).…”
Section: Individual-based Measure Of Genetic Variationsupporting
confidence: 68%
“…By integrating information about evolutionary and demographic processes, the distribution of genetic variation across a species' range can reveal critical insights about the viability of populations that is not necessarily represented in species occurrence or abundance patterns (Thomassen et al, 2010;Kovach et al, 2015). Understanding the distribution of intraspecific genetic variation and how it relates to environmental factors can assist better allocation of conservation resources and more robust predictions about species responses to environmental change (Frankel, 1974;Moritz, 2002;Vandergast et al, 2008;Scoble and Lowe, 2010;Thomassen et al, 2010;Sgrò et al, 2011;Gotelli and StantonGeddes, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of variance in allele frequency among locales (e.g., quantified using F ST or G′ ST ) provide a measure of β-genetic diversity among populations or collection locations. These estimates of genetic diversity can be used as response variables to assess how landscape features and disturbance influence persistence of aquatic species (e.g., Kovach et al 2015). Genetic data can also be used to estimate traditional ecological metrics (population size, movement, dispersal, etc.…”
Section: The Terminology and Purview Of Genetic Analysesmentioning
confidence: 99%
“…Climate change can effectively isolate populations by changing thermal or hydrologic regimes in different regions of rivers used by fish during different seasons and by different ontogenetic stages. Given overwhelming evidence for climate change and the likelihood that the scope of climate effects to fish populations will continue to expand, genetic data and analyses would help fisheries managers anticipate and mitigate these impacts (Landguth et al 2014;Kovach et al 2015). Genetic data will inform fisheries managers of population response to cryptic thermal barriers that decrease connectivity (i.e., reducing gene flow and thereby increasing genetic β-diversity, while also reducing effective population size and genetic α-diversity) and potentially identify the locations of these barriers to allow for management action.…”
Section: Integrating Evolutionary Concepts In Aquatic Assessment Progmentioning
confidence: 99%